"Use it or lose it": Characterization, implications, and mitigation of female infertility in captive wildlife. Issue 1 (28th December 2013) - Penfold, Linda M.; Powell, David; Traylor‐Holzer, Kathy; Asa, Cheryl S.
<x xml:space="preserve">Abstract</x> Zoos and other ex situ wildlife institutions can play an important role in species conservation by maintaining populations for education and research, as sources for potential re‐introduction or reinforcement, and as ambassadors for financial support of in situ conservation. However, many regional zoo associations are realizing that current captive populations are unsustainable, with many programs failing to meet demographic and genetic goals to ensure long‐term viability. Constraints on population size due to limited space often mandate delayed and/or less frequent breeding, but for females of many species this can have profound effects on fertility. A retrospective analysis combined with published literature and reliable anecdotal reports reveals that, when females are housed in a non‐breeding situation for extended periods of time, reproductive changes that negatively impact fertility have occurred in multiple species, including canids, elephants, white rhinoceros, Seba's bats, wildebeest, stingrays, and some felid species. Competing space needs and changing interest in taxa for exhibits over time compound the problem. Counter strategies to breed early and often have their own demographic and genetic consequences as well as logistical and political implications. Strategies to mitigate the sustainability crisis in these taxa might include a mixed strategy in which young, genetically valuable females are bred earlier and at more regular intervals to ensure reproductive success, in combination with the judicious use of available tools to manage the number of offspring produced, including contraception and culling. An understanding of the issues at stake is the first step towards developing management strategies for sustainable populations. Zoo Biol. 33:20–28, 2014. © 2013 Wiley Periodicals Inc.